Implementasi Jaminan Kesehatan Nasional (JKN) dalam Konteks Perlindungan Sosial dan Keamanan Nasional: Tinjauan Kritis Dimensi Keamanan Non Tradisional - Thamrin, Djuni (Jurnal Keamanan Nasional, 2018)
This paper argues that the concept of national security does not only consist of a traditional dimension but also encompasses non-traditional dimensions such as social, economic, and all significant forms that are free from fear, worry, danger, and threat. One of the important aspects of national security is health and social security in the form of policy tracking and its implementation of state policies that undertake a major transformation in the public health insurance system which is well known as the JKN, whose form in the community is known as BPJS